1976
DOI: 10.1099/00221287-96-2-351
|View full text |Cite
|
Sign up to set email alerts
|

Thin-layer Chromatographic Analysis of Mycolic Acid and Other Long-chain Components in Whole-organism Methanolysates of Coryneform and Related Taxa

Abstract: S U M M A R YAcid methanolysates of strains representing 58 coryneform taxa were examined for mycolic acids and other long-chain constituents by thin-layer chromatography. Mycolic esters were detected in the methanolysates of true corynebacteria but not in those from plant pathogenic bacteria, Corynebacterium haemolyticum, Corynebacterium pyogenes or from representatives of the genera Arthrobacter, Cellulomonas, Curtobacterium, Kurthia or Oerskovia. Thin-layer chromatography of whole-organism inethanolysates p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…Glucose was the principal sugar detected. The presence of mycolic acids was not determined in this study; however, Goodfellow et al (10) recently reported the absence of mycolic acids in a strain of KDB (H14) obtained from the U.S. Fish and Wildlife Service, Eastern Fish Disease Laboratory, Leetown, W.Va.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose was the principal sugar detected. The presence of mycolic acids was not determined in this study; however, Goodfellow et al (10) recently reported the absence of mycolic acids in a strain of KDB (H14) obtained from the U.S. Fish and Wildlife Service, Eastern Fish Disease Laboratory, Leetown, W.Va.…”
Section: Discussionmentioning
confidence: 99%
“…The most mobile fractions (Rp > 0.6) corresponded to methyl esters of long-chain fatty acids and the least mobile components were similar in their migration to methyl esters of mycolic acids isolated from strains of true corynebacteria (Minnikin et al, 1975;Goodfellow et al, Methyl esters of long-chain fatty acids were examined by gas chromatography ( Table 2). Each fatty-acid profile consisted mainly of mixtures of straight-chain and unsaturated components, but in extracts of two strains (B57 and ~5 9 ) small amounts of an unidentified component, possibly a C1, branched-chain ester, were detected.…”
Section: R E S U L T Smentioning
confidence: 99%
“…The mycolic acids which occur in true corynebacteria (Jones, 1975;Goodfellow et al, 1976) are of relatively low molecular weight (20 , 1970;Yano & Saito, 1972). At the other extreme, mycobacteria usually contain complex mixtures of mycolic acids (Minnikin, Alshamaony & Goodfellow, 1975) of high molecular weight (60 to go carbon atoms) (Etemadi, 1967).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the species bears little similarity to other animal pathogenic corynebacteria and its retention within the genus Corynebacterium has been questioned by several workers (Barksdale et al, 1957;Cummins & Harris, 1956;Barksdale, 1970;Goodfellow et al, 1976;Jones, 1975;Minnikin et al, 1978). In addition, the relationship of C. pyogenes to the species Corynebacterium haemolyticum (MacLean et al, 1946) remains unclear.…”
Section: Introductionmentioning
confidence: 99%